Tandem Macrolactone Synthesis: Total Synthesis of (−)‐Exiguolide by a Macrocyclization/Transannular Pyran Cyclization Strategy. (16th March 2022) - Mizukami, Daichi; Iio, Kei; Oda, Mami; Onodera, Yu; Fuwa, Haruhiko
Abstract: Tetrahydropyran‐containing macrolactones were synthesized by integrating Meyer–Schuster rearrangement, macrocyclic ring‐closing metathesis, and transannular oxa‐Michael addition under gold and ruthenium catalysis. Single‐step access to a variety of 14‐ to 20‐membered macrolactones containing a tetrahydropyran ring was possible from readily available linear precursors in good yields and with moderate to excellent diastereoselectivity. A 13‐step synthesis of (−)‐exiguolide, an anticancer marine macrolide, showcased the feasibility of our tandem reaction sequence for macrolactone synthesis and also demonstrated the power of transannular reactions for rapid assembly of the tetrahydropyran rings of the target natural product. Abstract : A catalytic tandem reaction integrating Meyer–Schuster rearrangement, macrocyclic ring‐closing metathesis, and transannular oxa‐Michael addition was developed to access tetrahydropyran‐containing macrolactones in a single step from readily available linear precursors. To illustrate the feasibility of the synthetic strategy, an antitumor marine macrolide, (−)‐exiguolide, was synthesized in just 13 steps from a commercially available compound.